2017
DOI: 10.1002/cncy.21844
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of next‐generation sequencing for the identification of clinically relevant variants in cytology smears in lung adenocarcinoma

Abstract: The data show a significantly higher likelihood of successful NGS with cytologic smears with more than 100 tumor cells. There was a trend for a higher NGS success rate with Pap smears versus DQ smears. Cancer Cytopathol 2017;125:398-406. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 21 publications
1
37
0
1
Order By: Relevance
“…A comparative evaluation of DNA extraction and targeted sequencing from 5 patients with FFPE-, Diff-Quik-, and PAP-stained FNA samples revealed that Diff-Quik outperformed PAP and FFPE material for DNA yields and single nucleotide variant calls [20]. Other studies compared the DNA integrity for genomic profiling from Diff-Quik- and PAP-stained slides and showed that PAP processing caused appreciable DNA degradation [26, 45]. Treece et al [50] showed significantly higher amplifiable DNA yields from FNA smears than from biopsies and FNA cell blocks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparative evaluation of DNA extraction and targeted sequencing from 5 patients with FFPE-, Diff-Quik-, and PAP-stained FNA samples revealed that Diff-Quik outperformed PAP and FFPE material for DNA yields and single nucleotide variant calls [20]. Other studies compared the DNA integrity for genomic profiling from Diff-Quik- and PAP-stained slides and showed that PAP processing caused appreciable DNA degradation [26, 45]. Treece et al [50] showed significantly higher amplifiable DNA yields from FNA smears than from biopsies and FNA cell blocks.…”
Section: Discussionmentioning
confidence: 99%
“…However, a practical issue involves the time required (> 24 to 48 h) to remove the coverslip (via soaking slides in xylene until the coverslip lifted) from the slides, thus affecting laboratory turnaround time [45]. To further optimise this process, it is possible to successfully remove coverslips from slides within 1 min using a recently described method of freezing the mounting media with liquid nitrogen [46].…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, a methodological study carried out on cell lines showed that Papanicolaou‐stained smears provided optimal DNA yield and fragment length . Notably, different studies reported that Diff‐Quik ® ‐stained slides are equivalent to CB sections and Papanicolaou slides for next‐generation sequencing (NGS) testing, without relevant variations in the total number of reads or in the percentage of reads aligning to the target region …”
Section: Direct Smearsmentioning
confidence: 99%
“…There is ample evidence on the equivalence and even the potential superiority of cytology specimens, whether from cell blocks or other cytology preparations, over tissue biopsies for the molecular testing of patients with NSCLC . PD‐L1 testing is a newer challenge, although it has been demonstrated that cell blocks also are comparable to histologic samples for the assessment of this biomarker .…”
Section: Potential Benefits Of Cytologymentioning
confidence: 99%
“…Despite current evidence and updated IASLC/CAP/AMP guidelines indicating the suitability of cytology samples for molecular characterization, tissue biopsies are still over‐represented in reported series on molecular testing . Reasons for this are likely multifactorial and may include: 1) limited awareness of the accuracy of molecular profiling using cytology specimens, 2) underestimation of the advantages of the cytology samples, 3) limited knowledge of or access to techniques for effectively optimizing small samples, and 4) the influence of other guidelines and registration trials that require tissue samples.…”
Section: Barriers To Implementationmentioning
confidence: 99%